2009
DOI: 10.1039/b822649k
|View full text |Cite
|
Sign up to set email alerts
|

Dimer-promoted fluorescence quenching of coralyne by binding to anionic polysaccharides

Abstract: The effects of anionic chondroitin or dextran sulfates on the absorption and fluorescence properties of coralyne, a cationic benzo[c]phenanthridine type alkaloid, were studied in aqueous solution. The remarkably strong binding to both polysaccharides promotes the coralyne dimer formation, which was evidenced by the changes in the absorption and fluorescence spectra and the fluorescence decay. The extent of dimerization, induced by chondroitin, shows a significant pH dependence because the competitive protonati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 29 publications
6
23
0
Order By: Relevance
“…Spectrophotometric measurements provided K D = 1.1×10 5 M −1 for the equilibrium constant of coralyne dimerization in water [16,18]. Due probably to its less extended aromatic structure, EH , which is close to the H D = 60 ± 2 kJ mol 1 value obtained for dimerization in the present work.…”
Section: Thermodynamics Of Dimerizationsupporting
confidence: 84%
See 1 more Smart Citation
“…Spectrophotometric measurements provided K D = 1.1×10 5 M −1 for the equilibrium constant of coralyne dimerization in water [16,18]. Due probably to its less extended aromatic structure, EH , which is close to the H D = 60 ± 2 kJ mol 1 value obtained for dimerization in the present work.…”
Section: Thermodynamics Of Dimerizationsupporting
confidence: 84%
“…For example, dimerization brought about 20-fold deceleration of the deactivation from the singlet-excited state for oxacarbocyanines [21], whereas almost 9-fold slowing down was found for a merocyanine dye [22]. The coralyne monomer and dimer had 9.7 and 40.7 ns fluorescence decay times, respectively [18].…”
Section: Effect Of Dimerization On the Fluorescence Characteristicsmentioning
confidence: 98%
“…We have demonstrated that the photophysical characteristics of Fla are solvent dependent. 36 The remarkable deuterium isotope effect on  f suggested that hydrogen bonding of the singlet-excited Fla offers an effective pathway for dissipation of excitation energy. The partial inclusion in the CB7 core provides a nonpolar, extremely nonpolarizable microenvironment for the guest 37 and diminishes its interaction with water decelerating thereby radiationless deactivation from the singlet-excited state.…”
Section: Methodsmentioning
confidence: 99%
“…There is a slightly better fit with three-exponential, which reveals a long lifetime component of about 30 ns which is in agreement with previous reports on coralyne dimers. 60 …”
Section: Resultsmentioning
confidence: 99%